Experimental Studies on State Self-Objectification: A Review and an Integrative Process Model - Kahalon, Rotem; Shnabel, Nurit; Becker, Julia C. (Frontiers in Psychology, 2018)
This paper provides an organizing framework for the experimental research on the effects of state self-objectification on women. We explain why this body of work, which had grown rapidly in the last 20 years, departs from the original formulation of objectification theory (Fredrickson & Roberts, 1997). We compare the different operationalizations of state self-objectification and examine how they map onto its theoretical definition, concluding that the operationalizations have focused mostly on one component of this construct (concerns about one’s physical appearance) while neglecting others (adopting a third-person perspective and treating oneself as a dehumanized object). We review the main findings of studies that experimentally induced state self-objectification and examined its affective, motivational, behavioral, cognitive, and physiological outcomes. We note that three core outcomes of this state as specified by objectification theory (safety anxiety, reduced flow experiences, and awareness of internal body states) have hardly been examined so far. Most importantly, we introduce an integrative process model, suggesting that the reported effects are triggered by four different mechanisms: appearance monitoring, experience of discrepancy from appearance standards, stereotype threat, and activation of the ‘sex object’ schema. We propose strategies for distinguishing between these mechanisms and explain the theoretical and practical importance of doing so.